Affective and discriminative touch: a reappraisal. (February 2022) - Morrison, India
Abstract : The role of CT afferents in affective touch is often viewed in contrast with the more well-established neural and functional systems supporting discriminative touch. However, a recent groundswell of evidence suggests that a categorical affective-versus-discriminative contrast may not bear scrutiny at all levels of the nervous system, especially when applied to finer-grained anatomical and functional relationships. Discrepancies in this evidence can be addressed by taking the layered phylogenetic history of specialized afferent systems into account, and how this history may have influenced functional integration within complex spinal circuits and brain networks in generating bodily states and behavior. This perspective inspires four proposed body-behavior reference frames, within which somatosensory-behavior relationships can be schematized in the nervous system of the behaving human: (1) proximal-distal (regarding the body axis and limbs, (2) somatic-skeletomotor (regarding efferent effectors) (3) reactive-predictive (regarding responses to external events); and (4) passive/receptive-active/motivated (with particular application to socially interactive behavior). Affective and discriminative functions can be dissociated at the extremes of these frame spaces without necessarily existing as discrete categories.